IN SILICO EVALUATION OF THE ENVIRONMENTAL, HUMAN AND PHARMACOKINETIC TOXICITY OF THE VETERINARY ANTIBIOTIC CEFQUINOMA - de Castro, Débora Marco; Motta, Luiz Frederico (Seven Editora, 2024)
The research developed in this work evaluated, through in silico methodologies, the environmental and human toxicity, the human oral bioavailability and pharmacokinetic parameters for the veterinary antibiotic Cefquinoma. Cefquinoma is a broad-spectrum antibiotic, classified as a fourth-generation cephalosporin. Currently, its use is intended for the treatment of clinical mastitis in lactating cows, caused by bacteria sensitive to it. Currently, the economic losses arising from the pathology result in several additional costs, such as a decrease in production and loss of the animal. Water and soil contamination are topics of high focus nowadays due to the possible impacts that antibiotic residues can cause in the environment. In view of this context, an in silico environmental toxicological study of Cefquinoma was carried out. The study revealed that the antibiotic is not toxic to bees and crustaceans, but it is toxic to fish, its chemical structure does not undergo environmental biodegradation, presenting a total removal rate of only 1.89%, resulting in contamination of the food chain and humans through food. Because the veterinary antibiotic promotes environmental, food and human contamination, it is mandatory to carry out the Toxicological and Pharmacokinetic study in silico human. This study indicated that the antibiotic is not available well via human oral use, as it violated three molecular descriptors of Lipinski’s Rule. The ADME in silico study revealed that the antibiotic has a low intestinal absorption rate, does not have permeability through the blood-brain barrier, and does not inhibit P-glycoprotein. The ADME in silico study also indicated that the antibiotic did not inhibit hepatic isoenzymes of the cytochrome P450 complex. The human in silico toxicological study revealed that the antibiotic is not mutagenic in terms of the AMES test, does not present carcinogenicity and in terms of acute oral toxicity it falls into category III (low toxicity), but presents respiratory toxicity, reproductive toxicity, mitochondrial toxicity and human nephrotoxicity. DOI:https://doi.org/10.56238/sevened2024.037-108